2011
DOI: 10.1071/mf10163
|View full text |Cite
|
Sign up to set email alerts
|

Business partner or simple catch? The economic value of the sicklefin lemon shark in French Polynesia

Abstract: Abstract. Most arguments invoked so far by the scientific community in favour of shark conservation rely on the ecological importance of sharks, and have little impact on management policies. During a 57-month study, we were able to individually recognise 39 sicklefin lemon sharks that support a shark-feeding ecotourism activity in Moorea Island, French Polynesia. We calculated the direct global revenue generated by the provisioning site, based on the expenses of local and international divers. The total yearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 34 publications
0
60
0
1
Order By: Relevance
“…The recognition that sharks can also provide financial benefits to communities beyond those provided by fishing has contributed to the perception of the value of sustaining the world's sharks. For example, Clua et al (2011) demonstrated that the tourism value of lemon sharks (Negaprion acutidens) could provide significant ongoing financial benefits to communities on Pacific islands over and above the one-off payment for catching and killing the sharks.…”
Section: The Effects Of a Changing Perception Of Sharksmentioning
confidence: 99%
“…The recognition that sharks can also provide financial benefits to communities beyond those provided by fishing has contributed to the perception of the value of sustaining the world's sharks. For example, Clua et al (2011) demonstrated that the tourism value of lemon sharks (Negaprion acutidens) could provide significant ongoing financial benefits to communities on Pacific islands over and above the one-off payment for catching and killing the sharks.…”
Section: The Effects Of a Changing Perception Of Sharksmentioning
confidence: 99%
“…By 2004 up to 2010, there were seven diving operators working in the same area, including six that were implementing artificial provisioning. A previous study on the economic value of shark-based ecotourism in Moorea island showed that around 4 000 local and 3 000 international divers were coming by the mid-2000s to Moorea every year with the specific purpose of viewing sharks, and an additional 5 600 were making the decision to dive with sharks while they were staying in Moorea [3].…”
Section: Resultsmentioning
confidence: 99%
“…For most of these countries, this type of ecotourism represents a critical source of income. In french Polynesia (Eastern-Central Pacific), environmental economists [3] have shown that any one of the 13 lemon sharks most often observed at a feeding site in Moorea (Windward islands) made an average contribution to the local economy of around USD 316 699 per year, contributing to a total income of US$5.4 million. However, given their elusive nature, encountering these shy species cannot be guaranteed, and artificial provisioning, generally called 'shark-feeding' , is necessary to ensure impressive aggregations of animals in specific places thereby allowing close interactions with divers and snorkellers [1].…”
Section: Determining the Role Of Hand Feeding Practices In Accidentalmentioning
confidence: 99%
“…Esta actividad de turismo con animales en vida silvestre se ha incrementado exponencialmente en los últimos 20 años (Higginbottom & Scott, 2008;Clua, Burray, Legendre, Mourier & Planes, 2011;Gallagher & Hammerschlag, 2011) y se promueve como una alternativa económica para la conservación de la naturaleza y de beneficios para las comunidades locales que reduce la presión sobre estos recursos en comparación al uso pesquero o deportivo (Topelko & Dearden, 2005;de Lacy & Whitmore, 2006;Gallagher & Hammerschlag, 2011;CisnerosMontemayor et al, 2013). En cuanto a esta práctica con tiburones y rayas, se destacan aquellas realizadas con Rhincodon typus, Manta birostris y algunas especies arrecifales como Carcharhinus perezi, Gynglimostoma cirratum o Dasyatis americana, las cuales son la base de actividades turísticas como avistamiento, alimentación y buceo.…”
unclassified